2002
DOI: 10.1046/j.1365-2567.2002.01389.x
|View full text |Cite
|
Sign up to set email alerts
|

Human monoclonal natural autoantibodies against the T‐cell receptor inhibit interleukin‐2 production in murine T cells

Abstract: SUMMARYNatural autoantibodies (NAAbs) specific for the T-cell receptor (TCR) are present in all human sera, but individuals with rheumatoid arthritis (RA) generally produce higher titres of immunoglobulin M (IgM) isotype autoantibodies (AAbs) against Vb TCR epitopes. To investigate possible correlations between the specificity of such AAbs and their role in immunomodulation, we generated seven B-cell hetero-hybridomas, secreting monoclonal IgM NAAbs, from the synovial tissue and peripheral blood of patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Anti-TCR antibodies may constitute another significant level of regulation, but their occurrence and regulatory role have been poorly investigated. Natural autoantibodies specific for the TCR are produced spontaneously at low levels in some healthy human sera, and at higher levels in patients with RA and SLE (34).…”
Section: Protective Antibodies In Autoimmune Diseasesmentioning
confidence: 99%
“…Anti-TCR antibodies may constitute another significant level of regulation, but their occurrence and regulatory role have been poorly investigated. Natural autoantibodies specific for the TCR are produced spontaneously at low levels in some healthy human sera, and at higher levels in patients with RA and SLE (34).…”
Section: Protective Antibodies In Autoimmune Diseasesmentioning
confidence: 99%
“…The murine monoclonals were synergistic with bacterial superantigens selective to different Vb subsets (Dehghanpisheh and Marchalonis, 1997). The human molecules did not induce apoptosis in T cells to which they bound, but inhibited the antigendriven production of the pro-inflammatory cytokine IL-2 (Robey et al, 2002b). The monoclonal antibodies used in these studies were of the IgM isotype, but IgG antibodies are normally produced as demonstrated by their presence in intravenous immunoglobulin preparations (Marchalonis et al, 1992b), by the finding that some human IgG myeloma proteins bind to T cell receptor V domain epitopes (Marchalonis et al, 1997a) and by our generation of IgG mAbs from peripheral B cells of individuals with SLE (Adelman, Schluter and Marchalonis, unpublished observations).…”
Section: Naturally Recognized Peptide Autoepitopes Of Tcr Variable Domentioning
confidence: 99%
“…FcγRIIb also down-regulated autoimmune plasma cell activation signals after cross-linking with activating FcR [26]. Considering that low level autoimmunity may well be required to maintain the diversity of adaptive immune responses [38,73], the balance between activation and inhibition of FcR functions is crucial in maintaining "tolerance" to self-antigens [45] and preventing inflammatory autoimmune disease. Animal models were particularly useful for investigating the role of FcγRIIb in auto-immunity and are discussed in more detail below.…”
Section: Roles Of Fcγrii In Autoimmune Diseasementioning
confidence: 99%